2001
DOI: 10.1182/blood.v97.9.2574
|View full text |Cite
|
Sign up to set email alerts
|

High response rate in refractory and poor-risk multiple myeloma after allotransplantation using a nonmyeloablative conditioning regimen and donor lymphocyte infusions

Abstract: Standard allogeneic stem cell transplant (allo-SCT) regimens have been associated with a high transplant-related mortality (TRM) in multiple myeloma (MM). Nonmyeloablative therapy can establish stable engraftment after allo-SCT and maintain the antitumor effect with less toxicity, which is important in heavily pretreated and elderly patients. We report on 16 poor-risk MM patients receiving allo-SCT from an HLA-matched (n ‫؍‬ 14) or mismatched (n ‫؍‬ 2) sibling following conditioning with melphalan 100 mg/m 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(103 citation statements)
references
References 21 publications
(14 reference statements)
2
94
2
5
Order By: Relevance
“…The delayed immune reconstitution following serotherapy with ATG may have been the cause of serious opportunistic infections observed in a proportion of patients, as previously observed in a study of patients receiving Campath-1H for GVHD prophylaxis . In addition, ATG administration may also lead to a reduced graft-versus-myeloma effect, which may explain the low rate of CR observed in the present study compared with other trials (Slavin et al, 1998;Badros et al, 2001;Giralt et al, 2001;Khouri et al, 2001;Michallet et al, 2001) and also progression during the first year post allograft documented in nine out of the 17 patients who could be evaluated.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The delayed immune reconstitution following serotherapy with ATG may have been the cause of serious opportunistic infections observed in a proportion of patients, as previously observed in a study of patients receiving Campath-1H for GVHD prophylaxis . In addition, ATG administration may also lead to a reduced graft-versus-myeloma effect, which may explain the low rate of CR observed in the present study compared with other trials (Slavin et al, 1998;Badros et al, 2001;Giralt et al, 2001;Khouri et al, 2001;Michallet et al, 2001) and also progression during the first year post allograft documented in nine out of the 17 patients who could be evaluated.…”
Section: Discussioncontrasting
confidence: 42%
“…One of the reasons for the acceptable TRM in this study was the low incidence of severe, acute GVHD. Other non-myeloablative conditioning regimens have been reported to be associated with a higher incidence of acute GVHD grade II-IV of 38-60% (Badros et al, 2001;Giralt et al, 2001;McSweeney et al, 2001). The in vivo use of ATG, with its prolonged half-life, as part of the conditioning regimen in our study might have contributed to the low incidence of GVHD.…”
Section: Discussionmentioning
confidence: 70%
“…Other authors have also reported a high rate of acute and chronic GvHD after prophylactic DLI. [32][33][34][35] A higher transplant-related mortality was reported in these studies after dose-reduced 32,33 as well as after standard high-dose conditioning. 34,35 The optimal time point and cell dose of DLI have not been established.…”
Section: Discussionmentioning
confidence: 74%
“…The infusion of donor lymphocytes after allo-SCT has proven relatively successful in the treatment of relapsing hematological malignancies. 16,17 In these cases, effective therapy is often based on the in vivo induction of T cells specific for minor histocompatibility antigens expressed in host-cells of hematological origin. 18 However, the incorporation of allo-SCT in the treatment of solid tumors has been less successful.…”
mentioning
confidence: 99%